Confirming the TMEM232 gene associated with atopic dermatitis through targeted capture sequencing - Jie Zheng (Nature Portfolio, 2021)
Abstract Atopic dermatitis (AD) is a common and complex skin disorder, and the 5q22.1 region had been reported to be associated with AD. To confirm the susceptibility gene for AD in the 5q22.1 region by haplotype and targeted capture sequencing. The haplotypes were reconstructed with the genotyping data of four SNPs and six deletions from 3624 Chinese Hans AD patients and 5076 controls. The targeted capture sequencing spanning 5q22.1 region was performed in the selected samples. The gene level enrichment analysis was done using loss of function variants. A total of 62 haplotypes were found, and the H15 haplotype had the strongest association with AD (P = 3.92 × 10−10, OR 0.17, 95% CI 0.09–0.32). However, no co-segregation mutation sites were found in the sequencing analysis within the 16 selected samples, while the enrichment analysis indicated that TMEM232 was significantly associated with AD (P = 7.33 × 10–5, OR 0.33, 95% CI 0.19–0.58). This study confirms previous findings that the TMEM232 gene is associated with AD by haplotype analysis and targeted capture sequencing.